2017
DOI: 10.3897/natureconservation.22.17369
|View full text |Cite
|
Sign up to set email alerts
|

A review of wildlife ecotourism in Manaus, Brazil

Abstract: The Amazon's ability to draw tourists is thought to be strongly associated with the opportunity to have sight of and interact with iconic wild animals. Tourism leaders are calling for the private and public sectors to develop wildlife focused ecotourism in this region. However, specific information regarding current practice and their impact on wildlife is lacking. Although wildlife ecotourism here remains in its relative infancy, our study demonstrates that a wide variety of wildlife-focused activities are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…This treats wild animals as photo props, to be exploited by tour operators and tourists alike for profit and as status symbols. Recent research by D'Cruze et al [72] has revealed that wildlife-focused activities in Amazonas, Brazil, allowed direct contact with animals 94% of the time. The use of animals as photo props for 'wildlife selfies' was particularly concerning, as researchers observed that animals involved-such as sloths, anacondas, and caimans-were poorly handled and subject to continual flash photography [72].…”
Section: Wildlife As Photo Propsmentioning
confidence: 99%
See 4 more Smart Citations
“…This treats wild animals as photo props, to be exploited by tour operators and tourists alike for profit and as status symbols. Recent research by D'Cruze et al [72] has revealed that wildlife-focused activities in Amazonas, Brazil, allowed direct contact with animals 94% of the time. The use of animals as photo props for 'wildlife selfies' was particularly concerning, as researchers observed that animals involved-such as sloths, anacondas, and caimans-were poorly handled and subject to continual flash photography [72].…”
Section: Wildlife As Photo Propsmentioning
confidence: 99%
“…Recent research by D'Cruze et al [72] has revealed that wildlife-focused activities in Amazonas, Brazil, allowed direct contact with animals 94% of the time. The use of animals as photo props for 'wildlife selfies' was particularly concerning, as researchers observed that animals involved-such as sloths, anacondas, and caimans-were poorly handled and subject to continual flash photography [72]. Research has shown that the capture, restraint, and repeated handling of animals in this manner induces fear and stress, causing physical and psychological damage [72].…”
Section: Wildlife As Photo Propsmentioning
confidence: 99%
See 3 more Smart Citations